Islamic Values of the Peta Kapanca Tradition at the Mbojo Tribe's Marriage, West Nusa Tenggara, Indonesia - Amrin Amrin; Muthoifin Muthoifin; Sudarno Shobron; Heldy Ramadhan Putra P (Universitas Muhammadiyah Magelang, 2020)
For the Bima people, the Mbojo tribe's Peta Kapanca tradition has very sacred symbols and meanings that must be carried out in every wedding procession. The Peta Kapanca tradition not only reveals a cultural identity and marriage tradition, but it also examines the Islamic values that are embedded in it. The objectives of this paper was to see how the Peta Kapanca tradition was carried out at Mbojo Tribe weddings in terms of procession and Islamic values. This is a descriptive qualitative study using an ethnographic approach. The findings show that the process of implementing the Peta Kapanca tradition at a Mbojo Tribe wedding is as follows: (1) the prospective bride sits on the stage (uma ruka), (2) the straight hand is placed on a pillow on the banana leaf, and the straight legs are straight and grounded with banana leaves, (3) the divine kalam is read, followed by the remembrance of Kapanca in the form of istigfar, creed, prayers, recitation of the verses of the Qur'an, and (4) crushing henna leaves which are mashed in the palms of the bride-to-be. This Peta Kapanca's cultural process contains good values such as aqidah, worship, and moral values.